Autosomal Recessive Hypercholesterolemia Caused by a Novel LDLRAP1 Variant and Membranous Nephropathy in a Chinese Girl: A Case Report - Feng, Siqin; Zhao, Xinyue; Wang, Yifei; Wang, Yiyang; Chen, Gang; Zhang, Shuyang (Frontiers in Cardiovascular Medicine, 2022)
Background Autosomal recessive familial hypercholesterolemia (ARH) is a very rare lipid metabolic monogenic disorder caused by homozygosity or compound heterozygosity for mutations in the low-density lipoprotein receptor adapter protein 1 (LDLRAP1) gene. It is a life-threatening disease characterized by markedly elevated low-density lipoprotein cholesterol (LDL-C), xanthomas, and premature coronary artery disease. Membranous nephropathy (MN) is less commonly observed in children. Here, the co-existence of ARH and MN was diagnosed in a Chinese girl. Case Presentation We present the case of a 13-year-old girl who was admitted with the typical symptom of nephrotic syndrome with an abnormally high serum LDL-C level. Gene sequencing revealed a novel homozygous LDLRAP1 variant (NM_015627: c.383 T>G, p.V128G), and the patient was diagnosed with ARH. A renal biopsy suggested that the nephrotic syndrome in the girl was induced by MN, but no evidence of secondary MN was found. A thorough examination was performed to explore the association between MN and ARH. Medical management with angiotensin receptor blockers and aggressive lipid-lowering treatment led to remission of proteinuria and clinical condition stabilization during 2-year follow-up. Conclusions This is the first case of co-existence of MN and ARH in a teenager carrying a novel pathogenic mutation of the LDLRAP1 gene (NM_015627: c.383 T>G, p.V128G).